THE PROCEDURES OF PHONOLOGICAL MODIFICATION IN THE ENGLISH AND INDONESIAN LANGUAGES - Bahagia Saragih; Barli Kifli; Fitria Ningsi; Naulida Situmeang; Novita Icha Pratiwi; Silviana Olivia; Syahrani Fathiansyah Hasibuan; Zaskia Az Zahra Nasution (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Phonological change is commonly experienced by bilingual students who use Indonesian and English in daily communication due to differences in the sound systems of both languages. This study aimed to analyze the phonological change processes experienced by second-semester students at Universitas Negeri Medan in Indonesian and English pronunciation, including the factors influencing these changes and students’ perspectives on phonology learning. This study applied a descriptive contrastive design. The data were obtained from the responses of 10 second-semester students taking Indonesian and English language courses at Universitas Negeri Medan. Data were collected using a structured close-ended questionnaire consisting of several sections related to pronunciation habits, phonological processes, influencing factors, and learning preferences. The collected data were classified based on phonological processes and analyzed descriptively using simple percentages. The findings showed that phonological changes frequently occurred in both languages. In Indonesian, deletion became the most dominant process, especially the omission of final sounds in informal speech. In English, epenthesis frequently appeared when students added vowel sounds to simplify consonant clusters. The study also revealed that first language interference, speaking habits, and limited corrective feedback influenced students’ pronunciation patterns. In addition, most students preferred practical pronunciation learning activities such as speaking exercises and direct correction. These findings imply that improving phonological awareness and providing more pronunciation practice are important to support bilingual learners in developing clearer and more accurate pronunciation.